Investigation of the Factors Hindering and Promoting Tourism Evidences from Villages of Abyaneh Village - Hoda Manafian (International Journal of Agricultural Management and Development, 2014)
Rural tourism, a dynamic industry with a promising future, can play a key role in economic improvement of talented countries such as Iran. Abyaneh village is one of the best-known villages in both Iran and the world. The number of annual visitors of this ancient village is approximately 550,000 that is a considerable number. Within a short radius of Abyaneh there are five villages (Barz, Tare, Komjan, Yarand, Hanjan) with a lot of potentials to develop rural tourism. But only 20% of tourists of Abyaneh population consider the surrounding villages as a separate destination. The large number of tourists visiting Abyaneh village provides opportunity for managing rural tourism in this area is to attract tourists to the surrounding villages around Abyaneh. In the present study, the hindering and promoting factors of fostering tourism in these villages have been compared by both the surrounded villagers' and locals' of Abyaneh village. To this end, 222 questionnaires were distributed among the individuals and the means were compared using Mann-Whitney test. The most important unfavorable factor, from the surrounded villagers' point of view, is lack of enough advertising and marketing and from the locals of Abyaneh village points of view, is the shortage of attractions, compared with attractions of Abyaneh.